Preparation method and application of cosmetic composite powder material

By preparing and modified rare earth-Zn-Ti-B-O composite powder material, combined with specific unit divisions and nanoparticles, the existing cosmetics powder material function is single and poor skin sensitivity. Ultraviolet light blocking and oil control effect.

CN119345071APending Publication Date: 2025-01-24YANGZHOU HUACHUOCHAI POWDER TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411489362.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing cosmetic powder materials have single functions and insufficient adhesion, which can easily lead to pore blockage, and poor ultraviolet light blocking function and skin sensibility.

Method used

By preparing the rare earth-Zn-Ti-B-O composite powder material and carried out unsecissions, the introduction of Silicine coupling KH570, β-cyclumonic monopoly cinematic choline, hydroxyl silicon oil and other structures, combined with nutmeg acid Magnesium and tea polyphenol polysaccharine nanometer can improve ultraviolet light blocking function and oil control effect.

Benefits of technology

The UV light blocking function has been improved, and the skin sensitivity and oil control effect have been improved, making the application of powder materials in cosmetics more ideal.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005099584260000081
    Figure BDA0005099584260000081
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a cosmetic composite powder material, and relates to the technical field of cosmetic powder materials.The preparation method comprises the following steps that S1, rare earth-Zn-Ti-B-O is prepared; s2, organic components of a silane coupling agent KH570, acrylamide beta-cyclodextrin quaternary ammonium salt, 2-methacryloyloxyethyl phosphorylcholine and vinyl hydroxyl silicone oil are modified; and S3, the organic component modified rare earth-Zn-Ti-B-O, magnesium myristate and the tea polyphenol chitosan nanoparticles are compounded. The cosmetic composite powder material disclosed by the invention is strong in ultraviolet light blocking function, good in skin feeling and good in oil control effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of cosmetic powder materials, and in particular to a preparation method of a cosmetic composite powder material and application thereof. Background Art

[0002] As society's aesthetic standards continue to improve, the beauty and skin care market is expanding, and the requirements for the convenience, comfort, ease of manufacture and performance of cosmetics are becoming higher and higher. Various powders are often used in cosmetics such as foundation, mascara, eye shadow or blush on the market to increase the durability, glossiness, moisturizing or concealing power of the above cosmetics on the skin. In order to achieve better beauty and skin care effects, the selection and matching of powder materials are extremely important.

[0003] Currently, cosmetic powder materials on the market mainly include organic powders such as organosilicon compounds, polyethylene, polyethylene terephthalate, nylon, poly(meth)acrylic acid or cellulose derivatives, or inorganic powders such as silicon dioxide or titanium dioxide. However, the above-mentioned cosmetic powder materials have more or less single functions, poor adhesion to human skin, and are easily aggregated by sweat and oil secreted by human skin, thereby blocking the user's pores and causing discomfort. They also have poor dispersibility and stability, limited oil absorption capacity, and are prone to technical defects such as dryness and dullness.

[0004] In order to solve the above problems, the Chinese invention patent with the authorization announcement number CN118286111B discloses a long-lasting oil-controlling non-drying modified composite powder and its preparation method. 100 parts of modified flaky powder; 20-30 parts of oil-absorbing powder; 2-5 parts of at least one of lauroyl lysine and lauroyl sarcosine; 1-3 parts of at least one of triethoxycaprylylsilane and polydimethylsiloxane; 10-15 parts of polymethyl methacrylate; the modified flaky powder is a mica powder synthesized by amino acid grafting with aminosilane; the oil-absorbing powder includes hydroxyapatite and zinc oxide composite powder; the composite powder is modified by a fluorine-containing silane coupling agent. The prepared powder has excellent long-lasting oil control, makeup holding, moisturizing, and non-drying effects. However, its skin feel needs to be further improved, and the UV blocking function still needs to be further improved. Summary of the invention

[0005] In order to overcome the defects in the prior art, the present invention provides a preparation method and application of a cosmetic composite powder material with strong ultraviolet light blocking function, good skin feel and good oil control effect.

[0006] The technical solution adopted by the present invention to solve the technical problem is: a method for preparing a cosmetic composite powder material, comprising the following steps:

[0007] Step S1, preparation of rare earth-Zn-Ti-BO: adding rare earth source, zinc source, titanium source, boron source and citric acid into water, mixing evenly, spray drying to obtain a precursor, then calcining the precursor, taking it out and grinding it, passing it through a 800-1300 mesh sieve to obtain rare earth-Zn-Ti-BO;

[0008] Step S2, modification of organic components: adding the rare earth-Zn-Ti-BO prepared in step S1, silane coupling agent KH570, acrylamide β-cyclodextrin quaternary ammonium salt, 2-methacryloyloxyethyl phosphorylcholine, vinyl hydroxy silicone oil, and initiator to an organic solvent, uniformly dispersing, stirring and reacting at 60-70° C. in an inert gas atmosphere for 3-5 hours, and spray drying to obtain rare earth-Zn-Ti-BO modified with organic components;

[0009] Step S3, powder compounding: the rare earth-Zn-Ti-BO modified by the organic component prepared in step S2, magnesium myristic acid, and tea polyphenol chitosan nanoparticles are mixed evenly, crushed, dried, sterilized, packaged, and stored to obtain a cosmetic composite powder material.

[0010] Preferably, in step S1, the rare earth source is cerium nitrate; the zinc source is at least one of zinc nitrate and zinc chloride; the titanium source is titanium nitrate; and the boron source is sodium borate.

[0011] Preferably, the mass ratio of the rare earth source, zinc source, titanium source, boron source, citric acid and water in step S1 is 0.1:(1-3):(0.8-1.2):(0.01-0.03):0.5:(10-20).

[0012] Preferably, the calcination temperature in step S1 is 600-850° C. and the calcination time is 4-6 hours.

[0013] Preferably, the mass ratio of the rare earth-Zn-Ti-BO, silane coupling agent KH570, acrylamide β-cyclodextrin quaternary ammonium salt, 2-methacryloyloxyethyl phosphorylcholine, vinyl hydroxy silicone oil, initiator, and organic solvent in step S2 is (70-80):(3-5):2:(3-5):4:(0.08-0.12):(200-250).

[0014] Preferably, there is no special requirement for the source of the acrylamide β-cyclodextrin quaternary ammonium salt. In one embodiment of the present invention, the acrylamide β-cyclodextrin quaternary ammonium salt is prepared according to the preparation method of reactive β-cyclodextrin quaternary ammonium salt in Example 6 of Chinese invention patent with authorization announcement number CN106008755B.

[0015] Preferably, the vinyl hydroxy silicone oil has a hydroxyl content of 6±0.5% (molar ratio) and a vinyl content of 6±0.5% (molar ratio), and is provided by Wuhan Huaxiang Kejie Biotechnology Co., Ltd.

[0016] Preferably, the initiator is azobisisobutyronitrile.

[0017] Preferably, the organic solvent is dichloromethane and hexanol in a weight ratio of (3-5):1.

[0018] Preferably, the inert gas is any one of nitrogen, helium, neon and argon.

[0019] Preferably, the mass ratio of the organic component-modified rare earth-Zn-Ti-BO, magnesium myristic acid, and tea polyphenol chitosan nanoparticles in step S3 is 100:(3-5):(1-3).

[0020] Preferably, there is no special requirement for the source of the tea polyphenol chitosan nanoparticles. In one embodiment of the present invention, the tea polyphenol chitosan nanoparticles are prepared according to the method of nanoparticle 2 in Example 1 of Chinese invention patent application number 201110037219.5.

[0021] Another object of the present invention is to provide a cosmetic composite powder material made by the above-mentioned preparation method of a cosmetic composite powder material for use in cosmetics such as foundation, mascara, eye shadow or blush.

[0022] The beneficial effects of adopting the above technical solution are:

[0023] (1) The preparation method of the cosmetic composite powder material provided by the present invention does not require special manufacturing equipment, has a simple process, high production efficiency, a safe and environmentally friendly manufacturing process, can be stably carried out in industrial production, and has a high value for promotion and application.

[0024] (2) The cosmetic composite powder material provided by the present invention is prepared by rare earth-Zn-Ti-BO to achieve uniform dispersion of zinc oxide and titanium oxide. The introduction of rare earth and B elements can improve the ultraviolet light blocking function and oil control effect. By modifying the organic components, silane coupling agent KH570, β-cyclodextrin quaternary ammonium salt phosphorylcholine, hydroxy silicone oil and other structures are introduced at the same time. They work together to effectively improve the ultraviolet light blocking function and skin feel, improve the oil control ability, and make the powder better compacted when used, without powder sticking and easy to disperse.

[0025] (3) The cosmetic composite powder material provided by the present invention is a compound of rare earth-Zn-Ti-BO modified by organic components, magnesium myristic acid and tea polyphenol chitosan nanoparticles. The composite powder material cooperates with each other to further improve the comprehensive performance and performance stability of the composite powder material, giving it a strong ultraviolet light blocking function, good skin feel, and good oil control effect. When used in cosmetics such as foundation, mascara, eye shadow or blush, it has good compatibility and matching performance with other components. DETAILED DESCRIPTION

[0026] In order to make the technical solution of the present invention better understood by the technical personnel in the field, and to make the above-mentioned features, purposes and advantages of the present invention more clearly understood, the present invention is further described below in conjunction with the embodiments. The embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.

[0027] Example 1

[0028] A method for preparing a cosmetic composite powder material comprises the following steps:

[0029] Step S1, preparation of rare earth-Zn-Ti-BO: adding rare earth source, zinc source, titanium source, boron source and citric acid into water, mixing evenly, spray drying to obtain a precursor, then calcining the precursor, taking it out and grinding it, passing it through an 800 mesh sieve to obtain rare earth-Zn-Ti-BO;

[0030] Step S2, modification of organic components: adding the rare earth-Zn-Ti-BO prepared in step S1, silane coupling agent KH570, acrylamide β-cyclodextrin quaternary ammonium salt, 2-methacryloyloxyethyl phosphorylcholine, vinyl hydroxy silicone oil, and initiator into an organic solvent, uniformly dispersing, stirring and reacting at 60° C. in an inert gas atmosphere for 3 h, and spray drying to obtain rare earth-Zn-Ti-BO modified with organic components;

[0031] Step S3, powder compounding: the rare earth-Zn-Ti-BO modified by the organic component prepared in step S2, magnesium myristic acid, and tea polyphenol chitosan nanoparticles are mixed evenly, crushed, dried, sterilized, packaged, and stored to obtain a cosmetic composite powder material.

[0032] The rare earth source in step S1 is cerium nitrate; the zinc source is zinc nitrate; the titanium source is titanium nitrate; the boron source is sodium borate; the mass ratio of the rare earth source, zinc source, titanium source, boron source, citric acid and water in step S1 is 0.1:1:0.8:0.01:0.5:10; the calcination temperature in step S1 is 600°C and the time is 4 hours.

[0033] The mass ratio of rare earth-Zn-Ti-BO, silane coupling agent KH570, acrylamide β-cyclodextrin quaternary ammonium salt, 2-methacryloyloxyethyl phosphorylcholine, vinyl hydroxy silicone oil, initiator, and organic solvent in step S2 is 70:3:2:3:4:0.08:200; the acrylamide β-cyclodextrin quaternary ammonium salt is prepared according to the preparation method of reactive β-cyclodextrin quaternary ammonium salt in Example 6 of the Chinese invention patent with authorization announcement number CN106008755B; the vinyl hydroxy silicone oil has a hydroxyl content of 6±0.5% (molar ratio) and a vinyl content of 6±0.5% (molar ratio), which is provided by Wuhan Huaxiang Kejie Biotechnology Co., Ltd.

[0034] The initiator is azobisisobutyronitrile; the organic solvent is dichloromethane and hexanol in a weight ratio of 5:1; the inert gas is nitrogen; the mass ratio of the organic component-modified rare earth-Zn-Ti-BO, magnesium myristic acid, and tea polyphenol chitosan nanoparticles in step S3 is 100:3:1; the tea polyphenol chitosan nanoparticles are made according to the method of nanoparticle 2 in Example 1 of the Chinese invention patent with application number 201110037219.5.

[0035] A cosmetic composite powder material prepared by the method for preparing the cosmetic composite powder material is used in cosmetics such as foundation, mascara, eye shadow or blush.

[0036] Example 2

[0037] A method for preparing a cosmetic composite powder material comprises the following steps:

[0038] Step S1, preparation of rare earth-Zn-Ti-BO: adding rare earth source, zinc source, titanium source, boron source and citric acid into water, mixing evenly, spray drying to obtain a precursor, then calcining the precursor, taking it out and grinding it, passing it through a 900 mesh sieve to obtain rare earth-Zn-Ti-BO;

[0039] Step S2, modification of organic components: adding the rare earth-Zn-Ti-BO prepared in step S1, silane coupling agent KH570, acrylamide β-cyclodextrin quaternary ammonium salt, 2-methacryloyloxyethyl phosphorylcholine, vinyl hydroxy silicone oil, and initiator to an organic solvent, uniformly dispersing, stirring and reacting at 63° C. in an inert gas atmosphere for 3.5 hours, and spray drying to obtain rare earth-Zn-Ti-BO modified with organic components;

[0040] Step S3, powder compounding: the rare earth-Zn-Ti-BO modified by the organic component prepared in step S2, magnesium myristic acid, and tea polyphenol chitosan nanoparticles are mixed evenly, crushed, dried, sterilized, packaged, and stored to obtain a cosmetic composite powder material.

[0041] The rare earth source in step S1 is cerium nitrate; the zinc source is zinc chloride; the titanium source is titanium nitrate; the boron source is sodium borate; the mass ratio of the rare earth source, zinc source, titanium source, boron source, citric acid and water in step S1 is 0.1:1.5:0.9:0.015:0.5:13; the calcination temperature in step S1 is 650°C and the time is 4.5h.

[0042] The mass ratio of rare earth-Zn-Ti-BO, silane coupling agent KH570, acrylamide β-cyclodextrin quaternary ammonium salt, 2-methacryloyloxyethyl phosphorylcholine, vinyl hydroxy silicone oil, initiator, and organic solvent in step S2 is 72:3.5:2:3.5:4:0.09:215; the acrylamide β-cyclodextrin quaternary ammonium salt is prepared according to the preparation method of reactive β-cyclodextrin quaternary ammonium salt in Example 6 of the Chinese invention patent with authorization announcement number CN106008755B; the vinyl hydroxy silicone oil has a hydroxyl content of 6±0.5% (molar ratio) and a vinyl content of 6±0.5% (molar ratio), which is provided by Wuhan Huaxiang Kejie Biotechnology Co., Ltd.

[0043] The initiator is azobisisobutyronitrile; the organic solvent is dichloromethane and hexanol in a weight ratio of 4.5:1; the inert gas is helium; the mass ratio of the organic component-modified rare earth-Zn-Ti-BO, magnesium myristic acid, and tea polyphenol chitosan nanoparticles in step S3 is 100:3.5:1.5; the tea polyphenol chitosan nanoparticles are made according to the method of nanoparticle 2 in Example 1 of the Chinese invention patent application number 201110037219.5.

[0044] A cosmetic composite powder material prepared by the method for preparing the cosmetic composite powder material is used in cosmetics such as foundation, mascara, eye shadow or blush.

[0045] Example 3

[0046] A method for preparing a cosmetic composite powder material comprises the following steps:

[0047] Step S1, preparation of rare earth-Zn-Ti-BO: adding rare earth source, zinc source, titanium source, boron source and citric acid into water, mixing evenly, spray drying to obtain a precursor, then calcining the precursor, taking it out and grinding it, passing it through a 1100 mesh sieve to obtain rare earth-Zn-Ti-BO;

[0048] Step S2, modification of organic components: adding the rare earth-Zn-Ti-BO prepared in step S1, silane coupling agent KH570, acrylamide-based β-cyclodextrin quaternary ammonium salt, 2-methacryloyloxyethyl phosphorylcholine, vinyl hydroxy silicone oil, and initiator to an organic solvent, and after uniform dispersion, stirring and reacting at 65° C. for 4 hours in an inert gas atmosphere, and spray drying, obtaining rare earth-Zn-Ti-BO modified with organic components;

[0049] Step S3, powder compounding: the rare earth-Zn-Ti-BO modified by the organic component prepared in step S2, magnesium myristic acid, and tea polyphenol chitosan nanoparticles are mixed evenly, crushed, dried, sterilized, packaged, and stored to obtain a cosmetic composite powder material.

[0050] The rare earth source in step S1 is cerium nitrate; the zinc source is zinc nitrate; the titanium source is titanium nitrate; the boron source is sodium borate; the mass ratio of the rare earth source, zinc source, titanium source, boron source, citric acid and water in step S1 is 0.1:2:1:0.02:0.5:15; the calcination temperature in step S1 is 750°C and the time is 5h.

[0051] The mass ratio of rare earth-Zn-Ti-BO, silane coupling agent KH570, acrylamide β-cyclodextrin quaternary ammonium salt, 2-methacryloyloxyethyl phosphorylcholine, vinyl hydroxy silicone oil, initiator, and organic solvent in step S2 is 75:4:2:4:4:0.1:230; the acrylamide β-cyclodextrin quaternary ammonium salt is prepared according to the preparation method of reactive β-cyclodextrin quaternary ammonium salt in Example 6 of the Chinese invention patent with authorization announcement number CN106008755B; the vinyl hydroxy silicone oil has a hydroxyl content of 6±0.5% (molar ratio) and a vinyl content of 6±0.5% (molar ratio), which is provided by Wuhan Huaxiang Kejie Biotechnology Co., Ltd.

[0052] The initiator is azobisisobutyronitrile; the organic solvent is dichloromethane and hexanol in a weight ratio of 4:1; the inert gas is neon; the mass ratio of the organic component-modified rare earth-Zn-Ti-BO, magnesium myristic acid, and tea polyphenol chitosan nanoparticles in step S3 is 100:4:2; the tea polyphenol chitosan nanoparticles are made according to the method of nanoparticle 2 in Example 1 of the Chinese invention patent application number 201110037219.5.

[0053] A cosmetic composite powder material prepared by the method for preparing the cosmetic composite powder material is used in cosmetics such as foundation, mascara, eye shadow or blush.

[0054] Example 4

[0055] A method for preparing a cosmetic composite powder material comprises the following steps:

[0056] Step S1, preparation of rare earth-Zn-Ti-BO: adding rare earth source, zinc source, titanium source, boron source and citric acid into water, mixing evenly, spray drying to obtain a precursor, then calcining the precursor, taking it out and grinding it, passing it through a 1200 mesh sieve to obtain rare earth-Zn-Ti-BO;

[0057] Step S2, modification of organic components: adding the rare earth-Zn-Ti-BO prepared in step S1, silane coupling agent KH570, acrylamide β-cyclodextrin quaternary ammonium salt, 2-methacryloyloxyethyl phosphorylcholine, vinyl hydroxy silicone oil, and initiator to an organic solvent, uniformly dispersing, stirring and reacting at 68° C. in an inert gas atmosphere for 4.5 hours, and spray drying to obtain rare earth-Zn-Ti-BO modified with organic components;

[0058] Step S3, powder compounding: the rare earth-Zn-Ti-BO modified by the organic component prepared in step S2, magnesium myristic acid, and tea polyphenol chitosan nanoparticles are mixed evenly, crushed, dried, sterilized, packaged, and stored to obtain a cosmetic composite powder material.

[0059] The rare earth source in step S1 is cerium nitrate; the zinc source is a mixture of zinc nitrate and zinc chloride in a mass ratio of 1:3; the titanium source is titanium nitrate; the boron source is sodium borate; the mass ratio of the rare earth source, zinc source, titanium source, boron source, citric acid and water in step S1 is 0.1:2.5:1.1:0.025:0.5:18; the calcination temperature in step S1 is 830°C and the time is 5.5h.

[0060] The mass ratio of rare earth-Zn-Ti-BO, silane coupling agent KH570, acrylamide β-cyclodextrin quaternary ammonium salt, 2-methacryloyloxyethyl phosphorylcholine, vinyl hydroxy silicone oil, initiator, and organic solvent in step S2 is 78:4.5:2:4.5:4:0.11:240; the acrylamide β-cyclodextrin quaternary ammonium salt is prepared according to the preparation method of reactive β-cyclodextrin quaternary ammonium salt in Example 6 of the Chinese invention patent with authorization announcement number CN106008755B; the vinyl hydroxy silicone oil has a hydroxyl content of 6±0.5% (molar ratio) and a vinyl content of 6±0.5% (molar ratio), which is provided by Wuhan Huaxiang Kejie Biotechnology Co., Ltd.

[0061] The initiator is azobisisobutyronitrile; the organic solvent is dichloromethane and hexanol in a weight ratio of 3.5:1; the inert gas is argon; the mass ratio of the organic component-modified rare earth-Zn-Ti-BO, magnesium myristic acid, and tea polyphenol chitosan nanoparticles in step S3 is 100:4.5:2.5; the tea polyphenol chitosan nanoparticles are prepared according to the method of nanoparticle 2 in Example 1 of the Chinese invention patent application number 201110037219.5.

[0062] Another object of the present invention is to provide a cosmetic composite powder material for use in cosmetics such as foundation, mascara, eye shadow or blush.

[0063] Example 5

[0064] A method for preparing a cosmetic composite powder material comprises the following steps:

[0065] Step S1, preparation of rare earth-Zn-Ti-BO: adding rare earth source, zinc source, titanium source, boron source and citric acid into water, mixing evenly, spray drying to obtain a precursor, then calcining the precursor, taking it out and grinding it, passing it through a 1300 mesh sieve to obtain rare earth-Zn-Ti-BO;

[0066] Step S2, modification of organic components: adding the rare earth-Zn-Ti-BO prepared in step S1, silane coupling agent KH570, acrylamide-based β-cyclodextrin quaternary ammonium salt, 2-methacryloyloxyethyl phosphorylcholine, vinyl hydroxy silicone oil, and initiator into an organic solvent, uniformly dispersing, stirring and reacting at 70° C. in an inert gas atmosphere for 5 hours, and spray drying to obtain rare earth-Zn-Ti-BO modified with organic components;

[0067] Step S3, powder compounding: the rare earth-Zn-Ti-BO modified by the organic component prepared in step S2, magnesium myristic acid, and tea polyphenol chitosan nanoparticles are mixed evenly, crushed, dried, sterilized, packaged, and stored to obtain a cosmetic composite powder material.

[0068] The rare earth source in step S1 is cerium nitrate; the zinc source is zinc nitrate; the titanium source is titanium nitrate; the boron source is sodium borate; the mass ratio of the rare earth source, zinc source, titanium source, boron source, citric acid and water in step S1 is 0.1:3:1.2:0.03:0.5:20; the calcination temperature in step S1 is 850°C and the time is 6 hours.

[0069] The mass ratio of rare earth-Zn-Ti-BO, silane coupling agent KH570, acrylamide β-cyclodextrin quaternary ammonium salt, 2-methacryloyloxyethyl phosphorylcholine, vinyl hydroxy silicone oil, initiator, and organic solvent in step S2 is 80:5:2:5:4:0.12:250; the acrylamide β-cyclodextrin quaternary ammonium salt is prepared according to the preparation method of reactive β-cyclodextrin quaternary ammonium salt in Example 6 of the Chinese invention patent with authorization announcement number CN106008755B; the vinyl hydroxy silicone oil has a hydroxyl content of 6±0.5% (molar ratio) and a vinyl content of 6±0.5% (molar ratio), which is provided by Wuhan Huaxiang Kejie Biotechnology Co., Ltd.

[0070] The initiator is azobisisobutyronitrile; the organic solvent is dichloromethane and hexanol in a weight ratio of 3:1; the inert gas is nitrogen; the mass ratio of the organic component-modified rare earth-Zn-Ti-BO, magnesium myristic acid, and tea polyphenol chitosan nanoparticles in step S3 is 100:5:3; the tea polyphenol chitosan nanoparticles are made according to the method of nanoparticle 2 in Example 1 of the Chinese invention patent application number 201110037219.5.

[0071] A cosmetic composite powder material prepared by the method for preparing the cosmetic composite powder material is used in cosmetics such as foundation, mascara, eye shadow or blush.

[0072] Comparative Example 1

[0073] A preparation method and application of a cosmetic composite powder material, which is basically the same as Example 1, except that no rare earth source, acrylamide-based β-cyclodextrin quaternary ammonium salt and magnesium myristic acid are added.

[0074] Comparative Example 2

[0075] A preparation method and application of a cosmetic composite powder material, which is basically the same as Example 1, except that no boron source, vinyl hydroxy silicone oil and tea polyphenol chitosan nanoparticles are added.

[0076] The performance of the composite powder material samples prepared by the preparation methods of the composite powder material for cosmetics described in Examples 1-5 and Comparative Examples 1-2 was tested. The test results are shown in Table 1. The test method is as follows:

[0077] (1) Bonding test: The composite powder material is dry-pressed into a 5 mm × 100 mm × 200 mm embryo under a pressure of 680 MPa, and then a drop test is carried out. The test platform is a square template with a thickness of 1.5 cm and a width of 30 cm. The embryo is dropped horizontally from a high place, and the maximum drop height at which the embryo is damaged is recorded; the larger the maximum drop height value, the better the bonding.

[0078] (2) Skin feel evaluation: 140 volunteers aged 25-35 were selected and randomly divided into 7 groups, each with 20 volunteers. The 7 groups of volunteers used the products of Examples 1-5 and Comparative Examples 1-2 respectively for 3 months, with each person using the products once a day on average. A satisfaction test was conducted, where the criteria for satisfaction with the use effect were that the foundation had good smoothness and spreadability when applied and was non-irritating to the skin; felt comfortable and breathable after use without dry lines; effectively kept the makeup from coming off, and had a whitening effect after a period of use. Satisfaction = number of satisfied people / total number of people × 100%.

[0079] (3) Ultraviolet absorbance evaluation: refer to the "Ultraviolet blocking effect measurement method and standard" in the "Related Regulations on the Review of Functional Cosmetics" (Announcement No. 2016-98 of the Food and Drug Safety Department) for evaluation, and use a solar simulator to measure SPF to confirm the UVB blocking effect. Specifically, 2 mg / cm 2 A sample is evenly applied on the skin, and after irradiating with an appropriate amount of UVB according to the minimum erythema dose without application for each subject, the minimum erythema dose (MED) is determined after a time difference of about 24 hours. SPF = MED of skin applied with powder material / MED of skin not applied with powder material. In the above formula, MED means the minimum erythema dose (time) required to cause erythema.

[0080] (4) Oil control ability: 70 healthy Asian female testers aged between 25 and 30 with normal oily skin were selected and randomly divided into 7 groups, with 10 people in each group. The test results were taken as the average value of each group. The testers washed their faces and applied lotion and cream under the same external environment under the same conditions. Then, the powder materials of Examples 1-7 and Comparative Examples 1-2 were applied to the faces of the testers in equal amounts. The skin oil secretion (μg / cm 2 ), and the average value of each group of subjects was used as the reorganized data.

[0081] Table 1

[0082]

[0083]

[0084] It can be seen from Table 1 that the cosmetic composite powder material disclosed in the embodiment of the present invention has better ultraviolet blocking property, binding property, oil control property and skin feel than the comparative example; the combined use of rare earth source, acrylamide β-cyclodextrin quaternary ammonium salt, magnesium myristic acid, boron source, vinyl hydroxy silicone oil and tea polyphenol chitosan nanoparticles is beneficial to improving the above properties.

[0085] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions only describe the principles of the present invention. The present invention may be subject to various changes and improvements without departing from the spirit and scope of the present invention. These changes and improvements fall within the scope of the present invention. The scope of protection claimed by the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing a cosmetic composite powder material, characterized in that: The steps include: Step S1, preparation of rare earth-Zn-Ti-BO: adding rare earth source, zinc source, titanium source, boron source and citric acid into water, mixing evenly, spray drying to obtain a precursor, then calcining the precursor, taking it out and grinding it, passing it through a 800-1300 mesh sieve to obtain rare earth-Zn-Ti-BO; Step S2, modification of organic components: adding the rare earth-Zn-Ti-BO prepared in step S1, silane coupling agent KH570, acrylamide β-cyclodextrin quaternary ammonium salt, 2-methacryloyloxyethyl phosphorylcholine, vinyl hydroxy silicone oil, and initiator to an organic solvent, uniformly dispersing, stirring and reacting at 60-70° C. in an inert gas atmosphere for 3-5 hours, and spray drying to obtain rare earth-Zn-Ti-BO modified with organic components; Step S3, powder compounding: the rare earth-Zn-Ti-BO modified by the organic component prepared in step S2, magnesium myristic acid, and tea polyphenol chitosan nanoparticles are mixed evenly, crushed, dried, sterilized, packaged, and stored to obtain a cosmetic composite powder material.

2. The method for preparing a cosmetic composite powder material according to claim 1, characterized in that: In step S1, the rare earth source is cerium nitrate; the zinc source is at least one of zinc nitrate and zinc chloride; the titanium source is titanium nitrate; and the boron source is sodium borate.

3. The method for preparing a cosmetic composite powder material according to claim 1, characterized in that: The mass ratio of the rare earth source, zinc source, titanium source, boron source, citric acid and water in step S1 is 0.1:(1-3):(0.8-1.2):(0.01-0.03):0.5:(10-20).

4. The method for preparing a cosmetic composite powder material according to claim 1, characterized in that: The calcination temperature in step S1 is 600-850° C. and the calcination time is 4-6 hours.

5. The method for preparing a cosmetic composite powder material according to claim 1, characterized in that: The mass ratio of rare earth-Zn-Ti-BO, silane coupling agent KH570, acrylamide β-cyclodextrin quaternary ammonium salt, 2-methacryloyloxyethyl phosphorylcholine, vinyl hydroxy silicone oil, initiator, and organic solvent in step S2 is (70-80):(3-5):2:(3-5):4:(0.08-0.12):(200-250).

6. The method for preparing a cosmetic composite powder material according to claim 1, characterized in that: The vinyl hydroxy silicone oil has a hydroxyl molar content of (6±0.5) %, and a vinyl molar content of (6±0.5) %.

7. The method for preparing a cosmetic composite powder material according to claim 1, characterized in that: The initiator is azobisisobutyronitrile; the organic solvent is dichloromethane and hexanol in a weight ratio of (3-5):1; the inert gas is any one of nitrogen, helium, neon and argon.

8. The method for preparing a cosmetic composite powder material according to claim 1, characterized in that: The mass ratio of the organic component-modified rare earth-Zn-Ti-BO, magnesium myristic acid, and tea polyphenol chitosan nanoparticles in step S3 is 100:(3-5):(1-3).

9. Use of a cosmetic composite powder material prepared by the method for preparing a cosmetic composite powder material according to any one of claims 1 to 8 in cosmetics such as foundation, mascara, eye shadow or blush.

Citation Information

Patent Citations

  • Preparation method and application of tea polyphenol chitosan nanoparticles

    CN102631472A

  • A reactive β-cyclodextrin quaternary ammonium salt, its preparation method and application

    CN106008755B

  • A long-lasting oil-controlling non-drying modified composite powder and preparation method thereof

    CN118286111B